Quality of public services as a mediator of competence and infrastructure for community satisfaction - Santoso, Budi; Martini, Ni Nyoman Putu (Universitas Muhammadiyah Yogyakarta, 2026)
This study analyzes the influence of the competence of government apparatus and infrastructure facilities on community satisfaction, with the quality of public services as a mediating variable in the Jember Regency Regional Secretariat. The research was conducted with a quantitative survey approach, involving 95 respondents who had directly interacted with public services, with data collected through online questionnaires and secondary documentation. The data were analyzed using WarpPLS Partial Least Squares (PLS-SEM), which enables testing of both direct and indirect relationships among variables as well as the validity and reliability of the measurement model. Research shows that the competence of the apparatus and the availability of infrastructure have a significant effect, both directly and through improving the quality of public services on public satisfaction. The quality of public services has proven to be an important mediating factor that strengthens the contribution of competencies and infrastructure facilities to increase public satisfaction. The findings show that apparatus competence and infrastructure availability have a significant effect on public satisfaction, both directly and indirectly through the quality of public services. Improving these three aspects should be treated as a strategic priority for the institution to strengthen organizational performance and optimize community satisfaction within the Jember Regency Regional Secretariat.